A Prognostic Model for Glioblastoma Patients Treated With Standard Therapy Based on a Prospective Cohort of Consecutive Non-Selected Patients From a Single Institution - Abedi, Armita Armina; Grunnet, Kirsten; Christensen, Ib Jarle; Michaelsen, Signe Regner; Muhic, Aida; Møller, Søren; Hasselbalch, Benedikte; Poulsen, Hans Skovgaard; Urup, Thomas (Frontiers in Oncology, 2021)
Background: Glioblastoma patients administered standard therapies, comprising maximal surgical resection, radiation therapy with concomitant and adjuvant temozolomide, have a variable prognosis with a median overall survival of 15 – 16 months and a 2-year overall survival of 30%. The aim of this study was to develop a prognostic nomogram for overall survival for glioblastoma patients treated with standard therapy outside clinical trials. Methods: The study included 680 consecutive, non-selected glioblastoma patients administered standard therapy as primary treatment between the years 2005-2016 at Rigshospitalet, Copenhagen, Denmark. The prognostic model was generated employing multivariate Cox regression analysis modeling overall survival. Results: The following poor prognostic factors were included in the final prognostic model for overall survival: Age (10-year increase: HR=1.18, 95% CI: 1.08-1.28, p<0.001), ECOG performance status (PS) 1 vs. 0 (HR=1.30, 95% CI: 1.07-1.57, p=0.007), PS 2 vs. 0 (HR=2.99, 95% CI: 1.99-4.50, p<0.001), corticosteroid use (HR=1.42, 95% CI: 1.18-1.70, p<0.001), multifocal disease (HR=1.63, 95% CI: 1.25-2.13, p<0.001), biopsy vs. resection (HR=1.35, 95% CI: 1.04-1.72, p=0.02), un-methylated promoter of the MGMT (O6-methylguanine-DNA methyltransferase) gene (HR=1.71, 95% CI: 1.42-2.04, p<0.001). The model was validated internally and had a concordance index of 0.65. Conclusion: A nomogram for overall survival was established. This model can be used for risk stratification and treatment planning, as well as improve enrollment criteria for clinical trials.